2023
DOI: 10.3390/antiox12051017
|View full text |Cite
|
Sign up to set email alerts
|

Natural Antimicrobials Promote the Anti-Oxidative Inhibition of COX-2 Mediated Inflammatory Response in Primary Oral Cells Infected with Staphylococcus aureus, Streptococcus pyogenes and Enterococcus faecalis

Abstract: Staphylococcus aureus, Streptococcus pyogenes and Enterococcus faecalis can colonize the tooth root canals, adhere to dentin walls, and frequently cause periodontitis in dogs. Bacterial periodontal diseases are common in domesticated pets, causing severe oral cavity inflammation and a strong immune response. This study investigates the antioxidant effect of a natural antimicrobial mixture (Auraguard—Ag) on the ability of S. aureus, S. pyogenes and E. faecalis to infect primary canine oral epithelial cells as w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 55 publications
1
7
0
Order By: Relevance
“…Ajose et al 2023, have recently reviewed ethnoveterinary medicinal plants and ethnoveterinary medicinal products utilised in dairy and livestock farming to combat mastitis, with the most prominent plants as Becium obovatum , Malva parviflora , Brucea antidysenterica , Acorus calamus L., Triticum sp, Arachis hypogeam , Peganum harmala , Citrus limon , Withania somnifera and others [ 8 ]. Among plant extracts, Sorghum phenol extract [ 5 ], sweet orange peel ( Citrus sinensis ), pomegranate ( Punica granatum ) [ 22 , 23 ], indian screw tree ( Helicteres isora ) [ 24 ], lemon balm ( Melissa officinalis ), a specie of laurel wood ( Knema retusa ) [ 25 ] and olive [ 13 ] extracts demonstrated strong antimicrobial activity against different S. aureus strains including other BM-associated pathogens. After in vitro disc diffusion assays from recent studies, the authors have reported the inhibitory zones against S. aureus significant average zones ranging from 22 to 31 mm [ 24 , 26 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Ajose et al 2023, have recently reviewed ethnoveterinary medicinal plants and ethnoveterinary medicinal products utilised in dairy and livestock farming to combat mastitis, with the most prominent plants as Becium obovatum , Malva parviflora , Brucea antidysenterica , Acorus calamus L., Triticum sp, Arachis hypogeam , Peganum harmala , Citrus limon , Withania somnifera and others [ 8 ]. Among plant extracts, Sorghum phenol extract [ 5 ], sweet orange peel ( Citrus sinensis ), pomegranate ( Punica granatum ) [ 22 , 23 ], indian screw tree ( Helicteres isora ) [ 24 ], lemon balm ( Melissa officinalis ), a specie of laurel wood ( Knema retusa ) [ 25 ] and olive [ 13 ] extracts demonstrated strong antimicrobial activity against different S. aureus strains including other BM-associated pathogens. After in vitro disc diffusion assays from recent studies, the authors have reported the inhibitory zones against S. aureus significant average zones ranging from 22 to 31 mm [ 24 , 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…The Knema retusa extract (KRe) showed significant antibacterial effects at observed MIC between 32 and 256 ug/mL and MBC between 64 and 512 ug/mL against S. aureus and S. haemolyticus , inhibiting biofilm formation and bacterial surface adherence [ 25 ]. In an earlier investigation, a natural antimicrobial mixture of organic acids, citrus and olive extracts was assessed for its anti-staphylococcal activity [ 13 ]. This blend manifested a multifaceted impact during the infection process.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The TGP cells were grown in Dulbecco’s Modified Eagle Medium (DMEM) (Cell Biologics, USA) as described above and maintained in 75cm 2 flasks (Sigma-Aldrich, Arklow, Ireland, SIAL0641) at 37 °C and 5% CO 2 . To test the effect of Aq on the ability of S. agalactiae to infect TGP cells, the assay was performed as previously described [ 17 ]. Briefly, the TGP cells (5.5 × 10 5 /well) were cultured for 24 h until 80–90% confluent in 6-well culture plates at pH 7.2.…”
Section: Methodsmentioning
confidence: 99%
“…Most biofilm-forming bacteria originate in the bacterial plaque formed on the tooth surface. The identification of biological agents and efficient control of biofilm formation and consequently dental plaque are of constant concern in the veterinary practice [ 30 ].…”
Section: Current Understanding Of Biofilm Formation In Animal Diseasesmentioning
confidence: 99%